PENGARUH CURRENT RATIO, DEBT TO EQUITY RATIO, RETURN ON EQUITY, NET PROFIT MARGIN DAN EARNING PER SHARE TERHADAP HARGA SAHAM (Study Kasus Pada Perusahaan Manufaktur Yang Terdaftar Di Bursa Efek Indonesia Periode 2008-2011) - Aditya Pratama; Teguh Erawati (Program Studi Akuntansi Fakultas Ekonomi Universitas Sarjanawiyata Tamansiswa, 2014)
This study discusses the stock price and financial ratios based on the financial statements of companies listed on the Indonesia Stock Exchange during the period 2008-2011. The purpose of this research was to determine whether the Current Ratio, Debt to Equity Ratio, Return on Equity, Net Profit Margin and Earning Per Share has an influence on the stock price. The company sampled as many as 20 of the 136 companies listed on the Indonesia Stock Exchange during the period 2008-2011. Using regression analysis, it can be seen that the variable current ratio, debt to equity ratio, return on equity, net profit margin and earnings per share to simultaneously have a significant influence on stock prices. Test results partially, current ratio, debt to equity ratio, and earnings per share positive and significant effect on stock prices. Return on equity has a negative effect on stock prices. Net profit margins and significant positive effect on stock prices. Keywords: Current Ratio, Debt To Equity Ratio, Return On Equity, Net Profit Margin, Earning Per Share, Stock Price.